Tei Industries Sdn Bhd / Ahmad Amirul Adlyi Mohamed - MOHAMED, AHMAD AMIRUL ADLYI (Faculty Of Chemical Engineering, 2021)
As a conclusion, a lot of things had happened to me during my internship days at TEI INDUSTRIES Sdn Bhd for the past 4 months or precisely 17 weeks. Some sort of things I had experienced in this company like how to deal with the real industry and I had gained many new knowledges that I did not study in the class previously. These new knowledges will give me benefits and it is also a precious opportunity for me to explore and gain knowledge in the engineering field before entering the real one soon. The real working industry is not an easy thing to deal with. Any single wrong move will surely turn into a disaster. In this company, I had learnt a very useful lessons which is to work safely although the work is urgent and need to be completed by the date, but the most important things is our safety and health because a wealth without health is nothing to be proud of. Next, during my internship period I have exposed to the real production line, I was a part of it. I also know the target of the company that always wanted the production to keep running no matter what it takes because a running production means that running of the income. It is a good thing because it can help in uprising the economy of the country and the people. Along my time in the industry, I had met with a few engineers which inspired me because of their skills and leadership. It makes me want to further my studies to become an engineer and be a good leader too. As for the recommendation, I hope that in the future TEI Industries Sdn, Bhd. can prepare a syllabus for the internship students to easier the internship students to understand the process without misunderstanding by learning on their own. There are a few misunderstandings that I have faced during the internship period for example the name of the components and the process flow. My friends and I had to take the initiatives to ask the staff ourselves in order to get a correct information on the products at the company. Other than that, the company just doing a wonderful job on the production of the high-quality product. Finally, in my point of view, all the theories that I had learnt during my studies cannot be seen clearly if I did not undergo this industrial field training. As for me, this practical period helps me to understand and increase my awareness towards the importance of electric and electronic production and I will appreciate and keep supporting local products. This is because, if we did not support our local product then no one else will. Again, I would like to wish a best of luck to TEI Industries Sdn. Bhd. and hope that this company will keep shines and strives to be the best in Malaysia and globally in making electric and electronic products that well known in the eyes of the world